Deep brain stimulation of the subthalamic nucleus in Parkinson's disease: From history to the interaction with the monoaminergic systems. (April 2017) - Faggiani, E.; Benazzouz, A.
Highlights: Non-human primate played a crucial role in the discovery of subthalamic deep brain stimulation therapy. Deep brain stimulation of the subthalamic nucleus dramatically improves the cardinal motor symptoms of idiopathic Parkinson's disease. Deep brain stimulation of the subthalamic nucleus is a safe therapy and the rate of serious psychiatric complications is very low. Degeneration of the monoaminergic systems may interact and alter the efficacy of subthalamic deep brain stimulation. Abstract: Parkinson's disease is the second most common neurodegenerative disorder, characterized by the manifestation of motor symptoms, which are mainly attributed to the degeneration of dopamine neurons in the pars compacta of substantia nigra. Based on advancements in the understanding of the pathophysiology of the disease, especially in animal models, the subthalamic nucleus has been pointed as a major target for deep brain stimulation in the treatment of motor symptoms, first developed in non-human primate and then successfully transfered to parkinsonian patients. Nevertheless, despite the focus on motor deficits, Parkinson's disease is also characterized by the manifestation of non-motor symptoms, which can be due to the additional degeneration of norepinephrine, serotonin and cholinergic systems. The pathophysiology of the non-motor symptoms is under studied and consequently not well treated. Furthermore, data from the literature about the impact of subthalamic deep brain stimulation on non-motor disorders are controversial and still under debate. Similarly, the risk of mood disorders post–deep brain stimulation surgery remains also controversial. Here, we review the clinical and experimental data of this neurosurgical approach on motor and non-motor behaviors and provide evidence for its interaction with the monoaminergic systems.